2008
DOI: 10.1038/eye.2008.84
|View full text |Cite
|
Sign up to set email alerts
|

Vitrectomy for diabetic macular oedema

Abstract: Aim To briefly review and discuss the literature on vitrectomy for diabetic macular oedema. Methods Literature review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 50 publications
0
36
0
2
Order By: Relevance
“…The reason why vitrectomy is effective in reducing angiogenic factors more rapidly than anti-angiogenic factors has not been determined, but two possibilities can be considered. First, there is an improvement of tissue oxygenation [17][18][19], and second, there is an increase in the diffusion of growth factors away from the retina [20]. It has been reported that hypoxia up-regulates both angiopoietin-2 [21] and HGF signaling [22].…”
Section: Discussionmentioning
confidence: 99%
“…The reason why vitrectomy is effective in reducing angiogenic factors more rapidly than anti-angiogenic factors has not been determined, but two possibilities can be considered. First, there is an improvement of tissue oxygenation [17][18][19], and second, there is an increase in the diffusion of growth factors away from the retina [20]. It has been reported that hypoxia up-regulates both angiopoietin-2 [21] and HGF signaling [22].…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6] However, for many patients, the chronic and recurrent nature of retinal diseases requires continued drug therapy after surgical procedure. [7][8][9] Experience with VEGF 10 and a number of drugs, including triamcinolone acetonide, 11,12 amphotericin B, 13 and 5-fluorouracil, 14 suggests that some drugs are cleared more rapidly in vitrectomized eyes. Indeed, further intravitreal pharmacologic treatment of posterior segment disease may be less effective after removal of the vitreous.…”
Section: Introductionmentioning
confidence: 99%
“…3 There may also be a role for vitrectomy surgery in the treatment of diabetic macular oedema with vitreomacular traction. 18 …”
Section: Surgical Indicationsmentioning
confidence: 99%